Between Memory And Political Activism: Nawal el Saadawi´S Contributions to Egyptian and Transnational Feminism - Luz, Flávia Abud (Malala, 2020)
From reflections on the work of Egyptian feminist and activist Nawal El Saadawi and the development of discussions between memory, trajectory and the pursuit of muslim women for rights in Middle Eastern and North African states the text aims to problematize the female agency focusing on issues such as the normatization of female bodies by tradition, the discussion of family laws, access to education, as well as the intersection between gender, culture and religion that is a feature of Nawal El Saadawi’s work.